PENERAPAN STRATEGI TALENT MANAGEMENT TERHADAP RETENSI KARYAWAN: STUDI PADA TOKO KOSMETIK JUN KOTA SOLOK - Ade Rahmat Ihsan; Fahrel Alfais. A; Hafidz Aima (Jurnal Riset Multidisiplin Edukasi, 2025)
Employee retention is a major challenge in retail businesses like cosmetic stores facing intense competition. This study aims to analyze the influence of implementing Talent Management strategies on employee retention at Toko Kosmetik Jun in Solok City. Using a quantitative approach and survey method involving store employees, the research examines the dimensions of succession planning, career development, and performance management in relation to employee retention intentions. The findings indicate that Talent Management strategies significantly contribute to improving employee retention rates, particularly through competency development and clear career pathways. This study offers strategic implications for HR practices in retail management to design sustainable talent policies.